New sweet potato network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A British consultant at the International Potato Centre (CIP) has established a network for her research resources on the sweet potato. The resources mainly concern biochemistry, nutrition, toxicity, post-harvest technology and animal feeding. Dr...